PENGARUH SYIAH DALAM KEHIDUPAN MASYARAKAT ACEH (Refleksi atas Naskah Hikayat Hasan Husain dan Nu>r Muhammad) - Fakhriati, Fakhriati (Universitas Islam Negeri Raden Intan Lampung, 2011)
Abstract The article examines the traces of ideology and practices of Shia teachings that developed in Indonesia, particularly Aceh by analyzing two popular texts in Acehnese society, especially the Pidie region, the story of Hasan and Husain and Nu r Muhammad. To this end, the author uses an interdisciplinary approaches; first it uses philology and codicology to assess the content and the physic of the manuscript. Then the inter-textual approach is used to compare the text of the manuscript with similar texts in order to obtain information related to the cultural practices of the Shia in Acehnese society. Then to analyze the context of the background and the existence of the manuscript appeared in the local community even its popularity it uses the approach of social history. The authors found that the two texts being studied describe that people were really appreciated and reflected history of the past, then they use it as a spirit in their lives. Persistent struggle and relentless fight the people of Aceh against in disbelief and colonialism, perhaps, was part of a reflection of genuine appreciation for the history of the struggle of ‘Ali and his family that they were praised in the saga.